Bridging Pedagogy and Technology: The Impact of Pancasila Project Understanding, Digital Literacy, and Teacher Competence on Digital Learning Content Creation - Susanto, Prasetyo; Dominica Niron, Maria; Saeed, Faisal (Papanda Publisher, 2025)
This study aims to examine the effects of understanding the Strengthening Pancasila Student Profile Project (P5), digital literacy, and pedagogical competence on teachers’ creation of digital learning content. A quantitative explanatory design was applied at an elementary school in Yogyakarta, Indonesia. Eighty-three teachers were selected using a simple random sampling technique. Data were collected through a structured questionnaire and analyzed using simple and multiple linear regressions. The findings reveal that understanding of P5 significantly influences digital content creation (β = 0.248), digital literacy emerges as the strongest predictor (β = 0.323), and pedagogical competence also shows a significant positive effect (β = 0.237). Collectively, the three variables explain 54.5% of the variance in teachers’ digital content creation (R² = 0.545). These results highlight the importance of integrating Pancasila values, digital literacy, and pedagogical skills to strengthen teachers’ capacity in implementing P5 through digital learning content. Future studies are recommended to explore supporting factors such as school leadership, infrastructure readiness, and teacher motivation.